The Role of Artificial Intelligence Applications in Supporting Sustainable Tourism Development: An Analytical Study in the Hotel Sector (Case Study: Babylon Hotel) - Muhsin Mahdi Rebat Al-kanany (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The global hotel industry is undergoing rapid digital transformation driven by artificial intelligence (AI) applications that support operational efficiency, guest experience, and sustainability. Specific Background: In the hospitality sector, AI technologies such as chatbots, virtual assistants, recommendation systems, and smart resource management tools are increasingly adopted to address rising customer expectations and environmental concerns. Knowledge Gap: Despite growing global attention, empirical evidence from Arab and Middle Eastern contexts, particularly Iraq, remains limited, with a lack of analytical studies assessing AI applications in sustainable tourism development. Aims: This study aims to examine the role of AI applications in supporting sustainable tourism development at the Babylon Hotel in Baghdad, focusing on guest satisfaction, service quality, and sustainability dimensions. Results: The findings reveal strong positive relationships between AI applications and guest satisfaction (r = 0.75), service quality (r = 0.80), and sustainability dimensions, including environmental (r = 0.68), economic (r = 0.72), and social (r = 0.65) aspects. Guests show high awareness and satisfaction with chatbots and personalized recommendations. Novelty: The study provides empirical evidence from the Iraqi hotel sector, addressing a regional research gap and integrating AI applications with the three dimensions of sustainability. Implications: The results highlight the importance of investing in digital infrastructure, developing AI-driven systems, and adopting sustainable resource management practices to support tourism development and operational performance. Highlights:• AI Tools Demonstrate Strong Association With Guest Satisfaction and Service Perception• Smart Systems Contribute to Environmental, Economic, and Social Sustainability Outcomes• Personalized Digital Services Receive High User Awareness and Acceptance Keywords: Artificial Intelligence, Sustainable Tourism, Hotel Industry, Guest Satisfaction, Environmental Sustainability.